Rapid and sustainable self-questionnaire for large-scale psychological screening in pandemic conditions for healthcare workers - Romero, Carolina Soledad; Otero, Maria; Lozano, Manuel; Delgado, Carlos; Benito, Ana; Catala, Juan; Iftimi, Adina; De Andres, Jose; Luedi, Markus M. (Frontiers in Medicine, 2023)
Background The pandemic caused by a coronavirus (COVID-19) has shocked healthcare systems worldwide. However, the psychological stressors remain unclear. The objective of this study was to assess the impact of a major pandemic on healthcare workers. We hypothesized that exposure to the virus would be the primary cause of psychological stress perceived by healthcare workers. Methods A national cross-sectional study conducted via an online questionnaire was distributed between April 9 and April 19, 2020 with a non-probabilistic sample technique. A structural equation model (SEM) was built with the variable ‘exposure to the virus’ and the Psychological Stress and Adaptation at work Score (PSAS). ‘Exposure to the virus’ was defined as the combined factors of ‘personal-sphere’, ‘work-related stress’ and ‘hospital characteristics’. A generalized linear model (GLM) was also tested. Results A total of 2,197 participants filled in the questionnaire and were analyzed. The exploratory factor analysis showed statistically significant variables related to the personal-sphere, work-related stress and the hospital’s characteristics, although the confirmatory factor analysis showed only the work-related stress factors to be significant. The GLM showed that personal-sphere-related variables (P<.001), stress at work (P<.001) and age (P<.001) were statistically significant. Conclusions Physical exposure to the virus is an essential factor that contributes to the psychological impact perceived during the pandemic. A combination of personal-sphere variables, work-related stress and hospital characteristics is a significant factor correlating with the degree of stress measured by PSAS, a new and fast instrument to assess stress in healthcare workers.